African swine fever virus vaccine development - Kumar, Rakshith (My University, 2025)
African swine fever virus (ASFV) is responsible for causing African swine fever (ASF), a highly contagious and economically devastating disease that affects domestic and wild pigs in the family Suidae. The ASFV is a large double-stranded DNA virus that replicates in cytoplasm of infected cells, primarily targeting macrophages, but it can also infect other cell types such as monocytes, dendritic cells, and endothelial cells. It has a genome size of about 170 – 193 kb and it is the only virus classified in the Asfarviridae family. The rapid spread of ASF in several regions in the world has caused severe economic losses in the swine industry, with cases reported in 63 countries and over 1.87 million pigs lost across Europe and Asia by the end of 2024. Unfortunately, there is no vaccine or treatment, and management of outbreaks entails implementation of strict biosecurity, rapid diagnosis, mass slaughter of infected and in-contact pigs with proper disposal, and disinfection measures to prevent transmission. The most promising vaccine candidates to date are attenuated ASFV strains, but several challenges, including potential reversion to virulence, immunosuppression, and limited cross-protection impede deployment. Subunit vaccines have potential to address some of the limitations associated with the attenuated ASFV vaccine candidates, but development of efficacious candidates has been hampered by lack of definition of correlates of immune protection, identification of protective antigens, and availability of a vector capable of effectively inducing protective immunity in pigs. To address these challenges, this study developed replication-competent adenovirus-vectored multicistronic ASFV antigen expression constructs encoding nearly 100% of the genotype II ASFV (Georgia 2007/1) proteome. Proteins expressed by these constructs were authenticated by using ASFV convalescent serum and a cocktail of the constructs, designated RC-Ad5-ASFV, formulated with or without Quil-A adjuvant, were evaluated in the following three treatment groups for safety, immunogenicity, and protective efficacy: i) RC-Ad5-ASFV with Quil-A adjuvant; ii) Modified RC-Ad5-ASFV (excluding ASFV structural proteins) with Quil-A adjuvant; and iii) RC-Ad5-ASFV without adjuvant. Immunization of commercial piglets induced strong ASFV-specific IgG responses that were significantly (p < 0.001) higher than the RC-Ad5-GFP negative controls. Post-boost sera from the vaccinees, but not from the negative controls, strongly recognized ASFV-infected primary swine cells. Interestingly, following challenge with the highly virulent ASFV (Georgia 2007/1) genotype II strain, five out of six pigs (p < 0.0001) immunized with the RC-Ad5-ASFV without adjuvant, successfully cleared the virus and were protected against the disease. Post-challenge, the survivors added ~2 lbs./day and they remained healthy at day thirty-nine when the study was terminated. Surprisingly, despite generating robust ASFV-specific IgG responses, the sera from these surviving pigs, similar to sera from the non-survivors, failed to neutralize, in vitro, infection of primary swine cells by the ASFV (Georgia 2007/1). Notably, ASFV-specific recall GrB⁺CD8[alpha]⁺ and Perf⁺CD8[alpha]⁺ T-cell responses post-challenge were detected in PBMCs from the survivors on days 26 and 33, and in splenocytes at study termination, suggesting a likely role for cellular immunity in viral clearance. MHC typing showed no correlation between SLA class I or II haplotypes and the protection observed in the survivors, suggesting that MHC background did not likely influence vaccine-induced protection under the tested conditions.
Keywords: African swine fever virus; Adeno viral vector vaccine; Multicistronic protein expression; Antibody responses; Granzyme B positive T cells; Histopathology